Islamic Stock Overreaction Phenomenon on Financial Statement: An Event Study - Satria Utama (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2021)
The purpose of this study is to examine whether there is an overreaction phenomenon in the announcement of financial statements during the observation period. The sample used in this study are stocks listed on the Indonesia Stock Exchange in the Jakarta Islamic Index (JII) category during the 2016-2018 period. T test results on the winner category stock prior to the announcement of the financial statement event which AAR value tends to be negative then AAR changed to positive on the date of the announcement of financial statements. On the contrary, AAR was seen to remain positive and statistically significant even to the 10th day after the announcement of the financial statements. After the announcement of the financial statements, investors do not appear to correct stock prices as an indication that they have overreacted. It’s shows that there was no reversal after the announcement of the financial statements. AAR loser and winner shares did not experience a reversal after the announcement of the financial statements. Results indicate that there is no overreaction phenomenon in the announcement of financial statements on the Indonesia Stock Exchange